Riding the Waves of Reforms in Corporate Law, an Overview of Recent Improvements in Italian Corporate Codes of Conduct - Nicoletta Ferro (Fondazione Eni Enrico Mattei (FEEM), 2006)
In the past only a few of the major Italian companies spontaneously adopted self- regulatory tools such as codes of corporate conduct or codes of ethics, claiming the set of values that should guide their conduct and their shareholders and stakeholders were called to comply with. As a reaction to national corporate scandals such as those involving Cirio and Parmalat, things started to change as the need for corporate governance reforms was felt at the institutional as well as at the corporate level. This new wave was mainly due to the enactment of Legislative Decree no. 231 of June 8 2001 by Italian Legislators that marked an important turning point for the Italian corporate regulatory framework as it made codes of ethics and codes of conduct a legal requirement for Italian companies rather than an additional public relations tool as they were generally considered by the business environment. The aim of this paper is to fill the information gap on the Italian corporate codes scenario and to foster the dissemination of knowledge about the current situation, giving an introductory sketch on Leg. Decree. 231/2001.
Keywords: F23; M14; 330; Code of Corporate Conduct; Codes of Ethics; Corporate Governance; Corporate Law; Corporate Governance; Gesellschaftsrecht; Italien